Palaeomagnetic cave stratigraphy of sediments from Hellemofjord, northern Norway - Løvlie, Reidar; Ellingsen, Kari Lise; Lauritzen, Stein-Erik (Geophysical Journal International, 1995)
Subglacial deposited sediments from three deep karst caves in Nordland, northern Norway, carry single-component palaeomagnetic directions interpreted to represent discrete records of palaeosecular variations (PSV) defining a clockwise rotation of the vector with time. The results suggest that preserved sediment sections commenced accumulating at the highest altitude in this cave system, consistent with an inverse stratigraphic sedimentation. Anomalously low inclinations are interpreted to represent a detrital remanent magnetization acquired at the time of deposition and affected by inclination error. The preservation of the inclination error in these sterile sediments is attributed to the absence of processes that may cause post-depositional alignment of magnetic grains. Non-systematic directional scatter is also attributed to poor smoothing of geomagnetic field variations in these cave sediments compared with lacustrine deposits. The ahnost closed PSV loop may represent discrete periods of sedimentation during one or, alternatively, several subglacial events. The PSV loop exhibits amplitudes in declination and inclination comparable with Holocene or Weichselian lacustrine PSV records. The minimum duration of sediment accumulation may be of the order of 400 to 1000 yr. If the investigated sediments represent succeeding records of geomagnetic secular variations during the last Late Weichselian glacial retreat, the reasonably good correlation with the PSV records from the Torreberga (Southern Sweden) varved clay sequence (12 200–10 200 bp) and UK lacustrine sediments (0–10 000 bp) tentatively suggests that the Rågge Javre Raigi sediments accumulated during the final Weichselian glacial retreat between 10 900 and 9 800 bp